Characterization of monomeric and soluble aggregated Aβ in Down's syndrome and Alzheimer's disease brains. (29th May 2021) - Gkanatsiou, Eleni; Sahlin, Charlotte; Portelius, Erik; Johannesson, Malin; Söderberg, Linda; Fälting, Johanna; Basun, Hans; Möller, Christer; Odergren, Tomas; Zetterberg, Henrik; Blennow, Kaj; Lannfelt, Lars; et al.
Highlights: The Aβ peptide pattern is generally similar in AD and DS, except the BACE1 site-spanning APP/Aβ peptides. N-truncated AβX-34, AβX-40, and AβX-42 peptides are more abundant in DS compared with AD. Protofibrils consist of Aβ1-40, Aβ1-42 and Aβ4-42, with higher relative abundance in AD and DS compared with controls. Abstract: The major characteristics of Alzheimer's disease (AD) are amyloid plaques, consisting of aggregated beta amyloid (Aβ) peptides, together with tau pathology (tangles, neuropil treads and dystrophic neurites surrounding the plaques), in the brain. Down's syndrome (DS) individuals are at increased risk to develop AD-type pathology; most DS individuals have developed substantial pathology already at the age of 40. DS individuals have an extra copy of chromosome 21, harbouring the amyloid precursor protein gene ( APP ). Our aim was to investigate the Aβ peptide pattern in DS and AD brains to investigate differences in their amyloid deposition and aggregation, respectively. Cortical tissue from patients with DS (with amyloid pathology), sporadic AD and controls were homogenized and fractionated into TBS (water soluble) and formic acid (water insoluble) fractions. Immunoprecipitation (IP) was performed using a variety of antibodies targeting different Aβ species including oligomeric Aβ. Mass spectrometry was then used to evaluate the presence of Aβ species in the different patient groups. A large number of Aβ peptides were identified including Aβ1-X, 2-X, 3-X, 4-X, 5-X, 11-X, and Aβ peptides extended N terminally of the BACE1 cleavage site and ending at amino 15 in the Aβ sequence APP/Aβ(-X to 15), as well as peptides post-translationally modified by pyroglutamate formation. Most Aβ peptides had higher abundance in AD and DS compared to controls, except the APP/Aβ(-X to 15) peptides which were most abundant in DS followed by controls and AD. Furthermore, the abundancies of AβX-40 and AβX-34 were increased in DS compared with AD. Aβ1-40, Aβ1-42, and Aβ4-42 were identified as the main constitutes of protofibrils (IP'd using mAb158) and higher relative Aβ1-42 signals were obtained compared with samples IP'd with 6E10 + 4G8, indicating that the protofibrils/oligomers were enriched with peptides ending at amino acid 42. All Aβ peptides found in AD were also present in DS indicating similar pathways of Aβ peptide production, degradation and accumulation, except for APP/Aβ(-X to 15). Likewise, the Aβ peptides forming protofibrils/oligomers in both AD and DS were similar, implying the possibility that treatment with clinical benefit in sporadic AD might also be beneficial for subjects with DS.